The Experience of Jewish Liturgy Studies Dedicated to Menahem Schmelzer. - Blank, Debra Reed. (Leiden : BRILL, 2011)
This edited collection honors Menahem Schmelzer's influence upon the field of Jewish liturgy. Three generations of scholars apply different analytical methods to varying texts and ritual occasions, providing an up-to-date picture of the field and its implications for related areas.
Description based upon print version of record.
Keywords: Judaism -- Liturgy -- History and criticism; Schmelzer, Menahem -- Contributions in Jewish liturgy; Schmelzer, Menahem, 1934-.; Religion; Schmelzer, Menahem, -- 1934- -- Contributions in Jewish liturgy; Judaism -- Liturgy -- History and criticism; RELIGION / Prayerbooks / Jewish; Electronic books